Do our diabetic patients ready for safe pregnancy? Attitude towards preconception care and its associated factors among women with diabetes attending Government Health Clinics in Terengganu - Mukhali, Hassan Basri; Nik Mahdi, Nik Nor Ronaidi; Abd Aziz, Aniza; Shalihin, Mohd Shaiful Ehsan; Jalaluddin, Anisah; Embong, Kasemani; Suhimi, Sunita (Universiti Putra Malaysia Press, 2022)
Introduction: Women with uncontrolled diabetes may conceive but will result in poor pregnancy outcomes. This study aimed to assess the level of knowledge and attitude and determine factors associated with attitude towards preconception care. Method: A cross-sectional study was conducted in various government health clinics from all districts in Terengganu by using multistage random sampling. A self-administered questionnaire was applied to assess the level of knowledge and attitude towards preconception care. Multiple logistic regressions were applied to determine factors associated with attitude towards preconception care. Results: A total of 422 respondents were involved. The prevalence of respondents with unsatisfactory knowledge and attitude were 41.7% and 84.1%, respectively. Knowledge was not significantly associated with attitude. Respondents who used contraception had a better attitude (Adj. OR: 0.44, 95% CI:0.23,0.84). Low household income was associated (Adj. OR: 2.40, 95% CI:1.10,5.26) with an unsatisfactory attitude towards preconception care. Conclusion: Attitude towards preconception care amongst diabetic women who were attending primary care clinics was unsatisfactory. A structured and focused preconception educational programme care is necessary, especially amongst low-income women.